2023
DOI: 10.3390/cancers15020424
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Various Ultrasound Risk Stratification Systems for Benign and Malignant Thyroid Nodules: A Meta-Analysis

Abstract: Background: To evaluate the diagnostic performance of ultrasound risk-stratification systems for the discrimination of benign and malignant thyroid nodules and to determine the optimal cutoff values of individual risk-stratification systems. Methods: PubMed, Embase, SCOPUS, Web of Science, and Cochrane library databases were searched up to August 2022. Sensitivity and specificity data were collected along with the characteristics of each study related to ultrasound risk stratification systems. Results: Sixty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The diagnostic performance of these two risk stratification systems has recently been assessed by two systematic studies; one concluded that neither of these guidelines is better than the other, while the other found that ACR TI-RADS is the most efficient risk stratification method [ 11 , 18 ]. In our study, the overall sensitivity of ACR TI-RADS was 72.3%, which was significantly higher than the ATA guideline’s sensitivity (49.2%, p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic performance of these two risk stratification systems has recently been assessed by two systematic studies; one concluded that neither of these guidelines is better than the other, while the other found that ACR TI-RADS is the most efficient risk stratification method [ 11 , 18 ]. In our study, the overall sensitivity of ACR TI-RADS was 72.3%, which was significantly higher than the ATA guideline’s sensitivity (49.2%, p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared ATA guidelines and the ACR TI-RADS to investigate how effectively they predict the presence of malignancy and how efficient they are at minimizing FNA biopsies [ 7 , 8 , 9 , 10 ]. However, these studies have employed distinct methodologies and achieved contradictory results [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid nodules are discrete lesions within the thyroid gland, which can be detected by ultrasonography ( 28 ). The incidence rate of thyroid nodules in women is four times that in men, and its incidence rate increases with age and body mass index ( 29 ).…”
Section: Co-occurrence Of Pcos and Thyroid Diseasementioning
confidence: 99%
“…Generally, only nodules>1 cm should be evaluated as they are more likely to become clinically significant cancers. In rare cases, some nodules<1 cm may lead to future incidence rate and mortality ( 28 ). Each thyroid nodule has an independent risk of malignancy, and patients with multiple nodules may need biopsy on multiple nodules.…”
Section: Co-occurrence Of Pcos and Thyroid Diseasementioning
confidence: 99%
“…2,3 However, there continues to be a lack of standardization in the use of these various RSSs for thyroid nodules, as well as in the clinical interpretation of their assigned values. [4][5][6] Additionally, distinguishing benign follicular adenomas from follicular carcinoma has posed a particular diagnostic dilemma, as they share many similar sonographic characteristics and may not be accurately stratified on RSSs. 7,8 Since follicular thyroid neoplasms cannot be distinguished on cytology, final diagnosis can only be made after surgical excision with microscopic examination for capsular or vascular invasion.…”
Section: Introductionmentioning
confidence: 99%